2015
DOI: 10.4193/rhin14.300
|View full text |Cite
|
Sign up to set email alerts
|

Reduced effect of intravenous antibiotic treatment on sinonasal markers in pulmonary inflammation

Abstract: This is the first publication demonstrating substantially lower effects of IV-antibiotic treatment on sinonasal than on pulmonary inflammatory markers. Consequently, our findings highlight limitations of systemic antibiotic treatment to control infection in the sinonasal compartment. Primarily, we attribute this to the paranasal sinus ́ structure: these hollow organs, which in bacterial sinusitis are frequently filled with pus, mucoeceles and polyps, are not reached effectively by systemic antibiotic treatment. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Reduction of TCC was found in NL and sputum, but only in sputum decreases reached statistical significance ( P = 0.005) as reported earlier in our group [ 48 ]. Similar results were found in protein concentrations; decline was seen in both airway levels, but again, only in the pulmonary compartment, changes reached statistical significance (protein LAW : P = 0.008) (see Figure 2(d) ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reduction of TCC was found in NL and sputum, but only in sputum decreases reached statistical significance ( P = 0.005) as reported earlier in our group [ 48 ]. Similar results were found in protein concentrations; decline was seen in both airway levels, but again, only in the pulmonary compartment, changes reached statistical significance (protein LAW : P = 0.008) (see Figure 2(d) ).…”
Section: Discussionsupporting
confidence: 89%
“…The UAW are coming into the clinical and scientific focus as they were identified as a reservoir for initial and persistent airway colonization with pathogens like S. aureus and P. aeruginosa, that can be followed by LAW colonization, inflammation, and deterioration [ 25 , 28 ]. Our previous studies assessed the correlation of colonization and inflammation in different airway compartments [ 16 , 20 , 47 , 48 ]. Here, we assessed changes in pathogen colonization, proteases, antiproteases, and cells as well as symptoms after elective IV-antibiotic treatments primarily directed against P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…This positive effect is strengthened by the tendency for serum antibodies to decrease after ESS with adjuvant therapy in both studies. Doth et al . reported substantially reduced effects of intravenous antibiotic treatment on sinonasal inflammatory markers as compared to the lungs.…”
Section: Discussionmentioning
confidence: 96%
“…Targeted treatment of sinonasal biofilms with long-term efficacy has not yet been described. Systemic antibiotics are limited in their treatment to control infection in the sinonasal compartment (20) . Weissman et al has previously shown that xylitol for sinonasal irrigation, a non-antibiotic inexpensive and a well-tolerated agent, resulted in greater improvement of symptoms of chronic rhinosinusitis compared to saline irrigation (21) .…”
Section: Wytske Fokkens Editor In Chiefmentioning
confidence: 99%